PREPARAÇÃO E CARACTERIZAÇÃO DE NANOPARTÍCULAS MAGNÉTICAS DE FERRITA DE COBALTO REVESTIDAS COM QUITOSANA/POLIETILENOGLICOL COMO CARREADORAS DE RESVERATROL - BURATTO, ANA PAULA (2023)
In this work, the conditions for obtaining magnetic cobalt ferrite nanoparticles coated with chitosan and polyethylene glycol containing resveratrol were evaluated using a 2³ factorial design. The variables studied were volume of oleic acid (2 - 8 mL), reaction time (30 - 90 min) and stirring speed (300 - 900 rpm) for the synthesis of magnetic cobalt ferrite (CoFe2O4) nanoparticles by co-precipitation chemical. The independent variables for obtaining polymeric nanoparticles were quantities of: chitosan (CS) (30, 60 and 90 mg), polyethylene glycol (PEG) (20, 40 and 60 mg) and sodium tripolyphosphate (STPP) (10, 20 and 30mg). The dependent variable was the average hydrodynamic size by dynamic light scattering. The condition of 30 mg of CS, 60 mg of PEG and 30 mg of STPP was ideal for obtaining polymeric nanoparticles with an average size of 184.6 nm, polydispersity index (PDI) 0.344 and Zeta potential +19.23 mV. X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) results confirmed the incorporation of CoFe2O4 into the polymeric nanostructure containing RSV. The nanoparticles showed an encapsulation efficiency of 98.75% with a slow and prolonged release rate of 33.49% in 120 h. The Hill-equation model presented the best fit (R = 0.949) for the mechanism of RSV release from nanoparticles. Furthermore, in three months of storage there was less than 10% degradation of RSV. The analytical method for the determination of RSV in nanoparticles was validated using UV-VIS spectroscopy. SEM analysis showed irregular morphology with flake-like particles of various sizes. Energy dispersive spectroscopy (EDS) analysis was important to confirm the presence of cobalt ferrite in the CS/PEG polymeric nanostructure. Thermal analysis indicated that the nanoparticles were more thermally stable than free resveratrol. The antioxidant activity of the nanoparticles was 170.55 mmol TE g-1 (ABTS) and 130.60 mmol TE g-1(DPPH). RSV-loaded nanoparticles inhibited the growth of four tested bacteria. The MIC and MBC values were < 52.36 ug mL-1, for both analyses. The cytotoxicity assay against human melanoma SK-MEL-28 and CCD-059sk tumor cells showed greater efficiency of the RSV nanoparticle compared to free resveratrol. The storage of apples sprayed with RSV nanoparticles resulted in fruits with a higher content of total phenolic compounds in the skin, and consequently greater antioxidant activity, which can promote longer shelf life and help reduce physical changes in the apples.